Transcriptomic Analysis of Potential “lncRNA–mRNA” Interactions in Liver of the Marine Teleost Cynoglossus semilaevis Fed Diets With Different DHA/EPA Ratios - Xu, Houguo; Cao, Lin; Sun, Bo; Wei, Yuliang; Liang, Mengqing (Frontiers in Physiology, 2019)
Long non-coding RNAs (lncRNA) have emerged as important regulators of lipid metabolism and have been shown to play multifaceted roles in controlling transcriptional gene regulation, but very little relevant information has been available in fish, especially in non-model fish species. With a feeding trial on a typical marine teleost tongue sole C. semilaevis followed by transcriptomic analysis, the present study investigated the possible involvement of lncRNA in hepatic mRNA expression in response to different levels of dietary DHA and EPA, which are two most important fatty acids for marine fish. An 80-day feeding trial was conducted in a flow-through seawater system, and in this trial three experimental diets differing basically in DHA/EPA ratio, i.e., 0.61 (D/E-0.61), 1.46 (D/E-1.46), and 2.75 (D/E-2.75), were randomly assigned to 9 tanks of experimental fish. A total of 124.04 G high quality genome-wide clean data about coding and noncoding transcripts was obtained in the analysis of hepatic transcriptome. Compared to diet D/E-0.61, D/E-1.46 up-regulated expression of 178 lncRNAs and 2629 mRNAs, and down-regulated that of 47 lncRNAs and 3059 mRNAs, while D/E-2.75 resulted in much less change in gene expression. The co-expression and co-localization analysis of differentially expressed (DE) lncRNA and mRNA among dietary groups were then conducted. The co-expressed DE lncRNA and mRNA were primarily enriched in GO terms such as Metabolic process, Intracellular organelle, Catalytic activity, and Oxidoreductase activity, as well as in KEGG pathways such as Ribosome and Oxidative phosphorylation. Overlap of co-expression and co-localization analysis, i.e., lncRNA–mRNA matches “XR_523541.1–solute carrier family 16, member 5 (slc16a5)” and “LNC_000285–bromodomain adjacent to zinc finger domain 2A (baz2a)”, were observed in all inter-group comparisons, indicating that they might crucially mediate the effects of dietary DHA and EPA on hepatic gene expression in tongue sole. In conclusion, this was the first time in marine teleost to investigate the possible lncRNA–mRNA interactions in response to dietary fatty acids. The results provided novel knowledge of lncRNAs in non-model marine teleost, and will serve as important resources for future studies that further investigate the roles of lncRNAs in lipid metabolism of marine teleost.